The change of the semantic layers of the concept of State in the era of Fath Ali Shahi (period of crisis and ambiguity) - Yousef Khanmohammadi; Davood Bayat (رهیافتهای سیاسی و بین المللی)
This Work shows the historical process of the appearance of the concept of State in the language of the Time in the first half of the thirteenth lunar century, the period of the successor to the founder of the Qajar dynasty. The central question of the research is that with the entry of Iran into its threshold period, to what extent the changes related to this crisis have a linguistic reflection in the application of the concept of State in the texts of that period, and which semantic layers are strengthened and which are deleted or Moved? Our claim that the old concept of the state in this period, for the first time in the heavy aura of ambiguity, with the anxiety resulting from the crisis of being on the threshold of historical time and facing the new concept; The ambiguity that in practice sounded the bell for the beginning of the end of the fixed and frozen concept of the state that claimed eternity. From this point on, the context of the fierce challenge between the two understandings of the old and new concepts of State gradually genesised. For this purpose, we will try to explore the semantic layers of the concept of State and their linguistic-expressive emergence in the face of the emerging crisis of the state, the crisis of the Iran-Russia wars, in the works of the authors of the period.